Linking friendship quality and peer group acceptance in adolescence - Pakalnienė, Edita; Barkauskienė, Rasa (Psichologija, 2006)
Peer acceptance and and friendships are different but related aspects of social relationships in adolescence (Bukowski at al., 1996). Friendship quality is considered as an essential element that describes friendship and it is easy to assess empirically. According to J. G. Parker and S. R. Asher (1993) it is defined as a complex of the six components: validation and care, conflict and betrayal, companionship and recreation, help and guidance, intimate exchange and confict resolution. This article deals with the relationship between peer group acceptance and friedship quality in adolescents. The aim of the study presented in this article was to examine the different aspects of friendship quality in young adolescents and delineate gender differences in the association between the sociometric status and friendship quality. The sample consisted of 225 adolescents aged 12 to 14. According to the J.D. Coie and K. A. Dodge (1983) technique of sociometric research the sample was divided into three subgroups: high, average and low accepted adolescents by peer group. All adolescents filled in the Frienddship Quality Questionnaire (Parker and Asher, 1989) as well as two additional questions that assess the friendship satisfaction. The results revealed different friendship quality patterns among low accepted and high-average accepted adolescents. Rejected adolescents showed low scores on Intimate exchange and Help and quidance subscales but other subscales’ scores did not differ significantly. The overal satisfaction with friendship was also significantly lower among rejected adolescents. Gender differences analysis revealed girls’ friendship quality scores being higher on all subscales. The more detailed analysis of gender differences in three subgroups according the sociometric status showed no differences among high, average and low accepted boys. However, low accepted girls showed lower scores on two subscales – Companionship and recreation and Help and guidance. Also, general satisfaction with their best friendship was lower when compared to average and high accepted girls. The results obtained are discussed in comparison with the findings of other uathors as well as interpreted within a framework of psychological characteristics that distinguish among adolescents with differing status in a peer group.